Micromagnetic Simulations of Permalloy Double-Dot Structures - Escrig-Murua, J; Tejo-Lazo, F; Corona-Gonzalez, R (Elsevier B.V., 2017)
In this paper we investigate by micromagnetic simulations the magnetic properties of Permalloy double-dot structures as a function of the center-to-center distance between the dots. Generally, a well-defined neck appears in the hysteresis curve, evidencing that the process of magnetization reversal occurs by nucleation and propagation of vortices. However, although the processes of magnetization reversal are similar for different distances between the dots, the coercivities are quite different, primarily due to the different energy contributions that dominate the system. The contribution of the shape anisotropy is important for Permalloy double-dot structures where the distance between the dots is less than their diameters, while the magnetostatic interaction between the two dots predominates if the distance between the dots is greater than their diameters. Finally, there is a critical distance for which the influence of magnetostatic interaction decreases sufficiently so that the interacting system can be considered as an isolated system. © 2017 Elsevier B.V.